Reintervention for stent occlusion after bilateral self‐expandable metallic stent placement for malignant hilar biliary obstruction. Issue 7 (21st April 2016) - Inoue, Tadahisa; Naitoh, Itaru; Okumura, Fumihiro; Ozeki, Takanori; Anbe, Kaiki; Iwasaki, Hiroyasu; Nishie, Hirotada; Mizushima, Takashi; Sano, Hitoshi; Nakazawa, Takahiro; Yoneda, Masashi; Joh, Takashi
Abstract : Background and Aim: Endoscopic reintervention for stent occlusions following bilateral self‐expandable metallic stent (SEMS) placement for malignant hilar biliary obstruction (MHBO) is challenging, and time to recurrent biliary obstruction (RBO) of the revisionary stent remains unclear. We aimed to clarify a suitable reintervention method for stent occlusions following bilateral SEMS placement for MHBO. Methods: Between 2002 and 2014, 52 consecutive patients with MHBO who underwent endoscopic reintervention for stent occlusion after bilateral SEMS placement were enrolled at two university hospitals and one tertiary care referral center. We retrospectively evaluated the technical and functional success rates of the reinterventions, and the time to RBO of the revisionary stents. Results: Technical and functional success rates of the reinterventions were 92% (48/52) and 90% (43/48), respectively. Univariate analysis did not determine any significant predictive factors for technical and functional failures. Median time to RBO of the revisionary stents was 68 days. Median time to RBO was significantly longer for revisionary SEMS placement than for plastic stent placement (131 days vs 47 days, respectively; log–rank test, P  = 0.005). Revisionary SEMS placement was the only independent factor that was significantly associated with a longer time to RBO of the revisionary stent in the multivariate Cox proportional hazards analysis (hazard ratio 0.37; 95% confidence interval 0.14–0.95; P  = 0.039). Conclusion: Revisionary SEMS placement is a suitable endoscopic reintervention method for stent occlusion following bilateral SEMS placement from the perspective of time to RBO of the revisionary stent.